2013
DOI: 10.1002/dmrr.2321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nordic walking on cardiovascular risk factors in overweight individuals with type 2 diabetes, impaired or normal glucose tolerance

Abstract: Nordic walking improved anthropometric measurements and exercise capacity. However, unsupervised Nordic walking may not provide a sufficient increase in exercise intensity to achieve ultimate health-promoting benefits on the cardiovascular parameters assessed in this study, particularly for those with disturbed glucose regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 32 publications
3
77
1
Order By: Relevance
“…Baseline characteristics of study participants have been previously reported (21,22). We have also reported changes in the clinical characteristics for this IGT cohort after 4 months of unsupervised Nordic walking (21,22).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Baseline characteristics of study participants have been previously reported (21,22). We have also reported changes in the clinical characteristics for this IGT cohort after 4 months of unsupervised Nordic walking (21,22).…”
Section: Resultsmentioning
confidence: 88%
“…The IGT cohort (n = 14) in the present investigation is a subgroup of a larger population of overweight, sedentary male and female volunteers who were recruited from Gustavsberg, a suburb of Stockholm, Sweden, to participate in a low-cost randomized controlled exercise intervention study with Nordic walking poles (21,22). Comprehensive details describing the entire study cohort have been published elsewhere (21,22).…”
Section: Study Participantsmentioning
confidence: 99%
See 3 more Smart Citations